Why Don't Languages Support Multimedia All the Way Down? - Guzdial, Mark (Communications of the ACM, 2012)
The author discusses the importance of providing programming languages that support multimedia, taken from his blog post "Why Don't Languages Support Multimedia All the Way Down," located at http://cacm.acm.org/blogs/blog-cacm/109917, from the "Communications of the Association for Computing Machinery (ACM)." He addresses the need for computer scientists to be able to shift levels of abstraction, the prominence of digital media usage in the 21st century, and the benefits of teaching computer programming language manipulation to students in an introductory computer science class.